A genome guided evaluation of probiotic bacteria from the Lactobacillus and Bifidobacterium genera - LAURA BAKER (2022)
Manipulating the microbiota has the potential to mitigate disease. Probiotics are currently a popular approach used to promote gut health. However, beneficial attributes are often strain-specific; therefore, an in-depth classification is valuable when evaluating such products. Here, the draft genomes of 16 bacteria (from the Lactobacillus and Bifidobacterium genera) are presented (referred to as CUL isolates), including: L.acidophilus (CUL21, CUL60), L.gasseri (CUL09), L.helveticus (CUL76), L.salivarius (CUL61), L.plantarum (CUL66, CUL66N), L.paracasei (CUL37, CUL07, CUL08), L.casei (CUL06), L.rhamnosus (CUL63), L.fermentum (CUL40, CUL67), B.bifidum (CUL20) and B.animalis subsp. lactis (CUL34). Furthermore, multi-locus sequence analysis revealed that CUL strains are novel entries into GenBank. Genomes were mined for beneficial and deleterious features of probiotic bacteria. As such, antibiotic resistance genes and phenotypic antibiotic resistance (ABR) profiles were established. Generally, most phenotypic resistance was linked to recognized resistance profiles e.g., kanamycin and chloramphenicol (in lactobacilli) and tetracycline (in bifidobacteria). However, ampicillin resistance was common, although a genomic basis was not established. Indeed, the correlation between genotype and phenotype was often low. In addition, when challenged with a combination of antibiotics and bile, a phenotypic shift from antibiotic-resistant to sensitive typically occurred. Interestingly, L.helveticus CUL76 developed enhanced resistance against chloramphenicol and vancomycin. Beneficial traits, including adherence, bile tolerance, and host interaction properties were identified in all CUL strains. L.helveticus CUL76 putatively encoded five bacteriocins, offering scope for future antimicrobial studies. Bile Salt Hydrolase (genes with bile tolerance and cholesterol reduction capabilities) were identified in several CUL species. L.plantarum CUL66N expressed bsh genes when challenged with bile and could reduce the bile acid pool (including free cholesterol) in vitro, indicating a bsh mediated, cholesterol-lowering capability of CUL66N.Here, the first in-depth genomic analysis of CUL strains is presented, allowing future research to continue using a genome-guided approach to evaluate health-promoting attributes of CUL bacteria.